2020
DOI: 10.1021/acs.inorgchem.0c01044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Biological Evaluation of a Second-Generation Multimodal Water-Soluble Porphyrin-RAPTA Conjugate for the Dual-Therapy of Cancers

Abstract: In this study we report the synthesis and biological evaluation of a novel cationic porphyrin-[Ru(η 6 -arene)(C2O4)PTA] (RAPTA) conjugate with potential as a multimodal dual-therapeutic agent. In the absence of high intensity light, relative to untreated cells our conjugate resulted in a 83% decrease in viable human adenocarcinoma cells at a concentration of 10 μM, which is significantly more active than the 57% decrease achieved with the same concentration of the unconjugated RAPTA complex alone. With a light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
(78 reference statements)
3
17
0
Order By: Relevance
“…The concentrations of RAPTA‐PANPs administered were based on the amount of RAPTA bound to the nanoparticles as previously determined by ICP‐MS analysis, allowing for a direct comparison between conjugated and unconjugated nanoparticles – administering equivalent quantities of NH 2 ‐PANPs allowed for direct comparison to evaluate if the anticancer properties were a function of the presence of the RAPTA complex. Treatment with 2 gave a typical dose–response profile as reported previously by Sandland et al [25] . NH 2 ‐PANPs appeared to have a minimal effect on cell viability (IC 50 >500 μM).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The concentrations of RAPTA‐PANPs administered were based on the amount of RAPTA bound to the nanoparticles as previously determined by ICP‐MS analysis, allowing for a direct comparison between conjugated and unconjugated nanoparticles – administering equivalent quantities of NH 2 ‐PANPs allowed for direct comparison to evaluate if the anticancer properties were a function of the presence of the RAPTA complex. Treatment with 2 gave a typical dose–response profile as reported previously by Sandland et al [25] . NH 2 ‐PANPs appeared to have a minimal effect on cell viability (IC 50 >500 μM).…”
Section: Resultssupporting
confidence: 77%
“…(Scheme 1, Scheme 2). Previous studies have demonstrated that 2 is associated with an IC 50 >500 μM when incubated with HT‐29 for 24 hours [25] …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Synthesis:[ Ru(h 6 -3-(p-tolyl)propanoic acid)PTA(C 2 O 4 )] (S1), [36] silver oxalate [42] and tert-butyl (2-aminoethyl)carbamate [43] were prepared according to literature procedures. Complex 6a was prepared as described by Sandland et al [44] 3-(4-Methylcyclohexa-1,4-dien-1-yl)propanoic acid:4 -Methylcinnamic acid (predominantly trans)( 21.54 g, 132.8 mmol) was added to as olution of NH 3 (1 L) and EtOH (100 mL) cooled at À78 8C, followed by further EtOH (100 mL). The resulting colourless solution was stirred with am echanical stirrer followed by the addition of lithium (8.51 g, 1.23 mol) piecewise (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis : [Ru(η 6 ‐3‐( p ‐tolyl)propanoic acid)PTA(C 2 O 4 )] ( S1 ), silver oxalate and tert ‐butyl (2‐aminoethyl)carbamate were prepared according to literature procedures. Complex 6 a was prepared as described by Sandland et al …”
Section: Methodsmentioning
confidence: 99%